WHAT DO WE NEED TO KNOW IN THE LOCAL GOVERNMENT TRANSFER PROCEDURE? - Ante Galić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In this paper, the author provides an overview of the most important legal provisions of the Law on Local and Regional Self-Government, the Law on Local Elections, the Law on the Transfer Procedure, the Law on Prevention of Conflicts of Interest, and other regulations relevant to the local government handover procedure.